Maqashid Sharia As The Basis For Decision Making Of Corporate Social Responsibility Based On A Prophetic Legal Paradigm - Hendar, Jejen (Prophetic Law Review, 2023)
In principle, corporate social responsibility (CSR) is a company’s commitment to participate in building a sustainable economy to improve the quality of life and the environment for the benefit of the company, the community, and the surrounding environment. In practice, however, many CSR programs are merely oriented towards the fulfilment of company obligations, which certainly affects the quality of CSR implementation. The prophetic legal paradigm is one perspective for carrying out activities derived from the divine order, based on three basic principles: amar ma’ruf (humanization), nahi munkar (an order to stay away from the things of faith and claimed disadvantages of Islam/liberation) and tu’minuna billah (transcendence). In this study these three principles are linked to the objectives of Islamic law known as maqashid sharia constituting different levels of implementation: dharuriyyat (essential needs), hajiyyat (complementary needs) and tahsiniyyat (tertiary needs).Keywords: CSR, Prophetic Law, Maqashid Syariah, decisions Maqashid Syariah Sebagai Dasar Pengambilan Keputusan Tanggung Jawab Sosial Perusahaan Berdasarkan Paradigma Hukum Profetik AbstrakPada prinsipnya, tanggung jawab sosial perusahaan (CSR) adalah komitmen perusahaan untuk berpartisipasi dalam membangun ekonomi berkelanjutan guna meningkatkan kualitas kehidupan dan lingkungan untuk kepentingan perusahaan, masyarakat, dan lingkungan sekitar. Namun dalam praktiknya, banyak program CSR yang hanya berorientasi pada pemenuhan kewajiban perusahaan, yang tentunya berdampak pada kualitas pelaksanaan CSR. Paradigma hukum profetik merupakan salah satu cara pandang untuk melaksanakan kegiatan yang bersumber dari perintah Tuhan, berdasarkan tiga prinsip dasar: amar ma'ruf (humanisasi), nahi munkar (perintah menjauhi hal-hal yang bersifat keimanan dan mengklaim merugikan Islam/ pembebasan) dan tu'minuna billah (transendensi). Dalam kajian ini ketiga prinsip tersebut dikaitkan dengan tujuan hukum Islam yang dikenal dengan maqashid syariah yang memiliki tingkatan pelaksanaan yang berbeda: dharuriyyat (kebutuhan esensial), hajiyyat (kebutuhan pelengkap) dan tahsiniyyat (kebutuhan tersier).Kata kunci: CSR, Hukum Nabi, Maqashid Syariah, keputusan.